Lectura de pictogramas para desarrollar la capacidad de expresión oral en niños y niñas del subnivel 2 de educación inicial; de 4 a 5 años del centro de educación inicial “El Trencito del Conocimiento” del cantón cayambe, provincia Pichincha, periodo 2021-2022. - López Fernández, Katherin Nicol (2022)
The purpose of this work is to carry out a study on the use of pictograms for the development of oral expression skills in children of sublevel 2 of initial education. Therefore, it is necessary to make an approach to reality about the current situation that we are going through, in the same way this research is clearly linked to teachers and their families to establish the causes that originate the problem. In the same way, analyze the teaching staff and the use of didactic material that the institution has. The reading of pictograms improves the forms of communication and relationship of children with the world around them, which requires stories with pictograms, images that catch their attention to enrich the linguistic intelligence of children. In this way, knowing the methodology that we have to apply to favor reading in children, to make them understand what we want to interpret through an image, the appropriate use of pictograms makes the teacher through visual activities, it strengthens the attention span of children intellectually, spontaneously, voluntarily, while linguistic intelligence matures substantially. From this fact arises the need to use pictograms for the development of reading from an early age. KEY